2021
DOI: 10.1002/nau.24677
|View full text |Cite
|
Sign up to set email alerts
|

Animal experimental research assessing urogynecologic surgical mesh implants: Outcome measures describing the host response, a systematic review and meta‐analysis

Abstract: Aim Before the introduction of new biomaterials for prolapse surgery, animal studies on the host response are required. Unfortunately, large variation in study design hampers obtaining an overview of the safety and efficacy, and translation to clinical practice. Our aim is to systematically review the literature on all outcome measures describing the host response in animal studies assessing the biocompatibility of urogynecologic surgical mesh implants for prolapse surgery. Furthermore, by meta‐analysis, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(61 reference statements)
1
7
0
1
Order By: Relevance
“…Extensive histological analysis revealed higher levels of inflammatory cell infiltration, vascularization, and FBGC formation in mice with a biomaterial as compared to sham mice, confirming previous observations [ [42] , [43] , [44] , [45] , [46] ]. It is known that denser implants with smaller pores induce a more pronounced or prolonged inflammatory response as compared to lighter implants with larger pores [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Extensive histological analysis revealed higher levels of inflammatory cell infiltration, vascularization, and FBGC formation in mice with a biomaterial as compared to sham mice, confirming previous observations [ [42] , [43] , [44] , [45] , [46] ]. It is known that denser implants with smaller pores induce a more pronounced or prolonged inflammatory response as compared to lighter implants with larger pores [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…Thirdly, we used relatively high doses and a monoculture of S. aureus bacteria whereas the vaginal flora in women is multimicrobial and also contains non-pathogenic commensals. And finally, the host response is also dependent on the site of implantation because this response has been shown to significantly differ in the vagina as compared to the abdomen [ 46 ], so this should be taken into account when interpreting these results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our research group has extensive experience with the evaluation of physiologic changes in the vagina and pelvic floor, including a variety of outcome measures and innovative technologies. [22][23][24][25][26][27] Also for this study, we devised an innovative way to determine the mean epithelial thickness of the vaginal wall, which provided a solid and representative value for our primary outcome. In addition, the 4-point grading scale, used for histology assessment, was determined from the data available from this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Even though implants are initially designed to surgically correct POP and provide mechanical support to the pelvic tissues, ideally they should induce a foreign body response that results in the development of new connective tissue that is mechanically self-sufficient to support descending organs [ 18 , 26 ]. Animal studies in which vaginal implant surgeries were performed indicated that healing response, vascularization, and collagen metabolism are increased, and consequently increase the mechanical properties of the tissue as compared to NTR [ 27 ].…”
Section: Introductionmentioning
confidence: 99%